The effect of injection pressure on the droplet size distributions and micro-explosion / Mhadi A. Ismael ... [et al.] - A. Ismael, Mhadi; R. Heikal, Morgan; A. Aziz, A. Rashid; El-Adawy, Mohammed (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Emulsion droplet size plays a key role in the micro-explosion occurrence as well as the stability of the emulsion. In a high-pressure common rail system, the water-in-diesel emulsion is subjected to intense pressure, temperature and shear when passing through the common rail and injector nozzle thereby altering the droplet size distributions as well as the number of droplets. Water emulsified diesel made with 15% of water content by volume was visualized under the microscope before and after the injector nozzle at an injection pressure of 1500 bar. The size and number of the dispersed water droplets were measured using a developed Matlab image processing code. The influences of the size of the dispersed water droplets before and after the injection on the micro-explosion phenomenon were examined using a hot plate technique. A high-speed camera and thermocouple were synchronized to record the images and the temperature of the emulsion droplet. The results indicate that micro-explosion of the emulsion droplets was significantly affected by the injector shearing. Thereby the reduction in the size of the dispersed water droplets resulted in an increase in temperature required to initiate micro-explosion and delayed its onset.